Virgin Coconut Oil (VCO) Accelerated Wound Healing Process in Diabetes mellitus (DM) Patients With Diabetic Ulcer in dr. Rasidin Hospital, Padang, Indonesia - Dafriani, Putri; Nur, Siti Aisyah; Morika, Honesty Diana; Marlinda, Roza (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
DM ulcer is one of the complications of DM that resulted in amputation even death. A DM ulcer usually a chronic wound which difficult to heal with antibiotics because of the presence of the Staphylococcus bacteria resulting in an antibiotic-resistant ulcer, requiring an alternative as the solution. VCO, one of the natural materials that are easily acquired have benefits for wounds and often used by the community. VCO contains lauric acid and flavonoids compounds work as antibacterial, anti-inflammatory, antioxidant, and analgesic. The purpose of this study is to determine the benefits of VCO on the healing of DM ulcers. This was a quasi-experiment study recruited 16 DM patients with ulcers treated at the Dr. Rasidin Hospital, Padang, Indonesia. The study participants are divided into 2 groups, 8 patients in the control group, and another 8 in the intervention group. The control group is given wound care using NaCl 0.9% and the intervention group carried out wound care with NaCl 0.9% plus VCO. VCO is produced using a stimulation technique. Wound care is performed for 4 days in both groups and the surface area of the wound is calculated after 4 days then the data precede using independent t-test. The results of the study showed a meaningful difference in surface wound between the control group and the intervention group with the value P = 0,033. VCO helps wound healing by reducing the surface area of the wound.